GAMBARAN FAKTOR PENOLAKAN SEMENTARA PADA CALON PENDONOR LAKI-LAKI DAN PEREMPUAN DI UDD PMI KABUPATEN MALANG TAHUN 2024: OVERVIEW OF TEMPORARY BLOOD DONATION DEFERRAL FACTORS IN MALE AND FEMALE DONORS AT UDD PMI MALANG DISTRICT IN 2024 - Karimah, Hania Dinda; Ariani, Nia Lukita; Yuliwar, Roni (STIKes Maharani Malang, 2025)
Introduction: Men and women have an equal chance of experiencing temporary blood donation deferral. This has an impact on the unavailability of blood because the blood supply for transfusion is insufficient. This study aims to determine the description of temporary blood donation deferral factors in male and female donor candidates at the PMI UDD in Malang Regency in 2024. Method: A documentary study by taking secondary data from blood donation deferral forms that experienced temporary blood donation deferral in male donor candidates totaling 2263 data and in female donor candidates totaling 2491 data at the PMI UDD in Malang Regency in January-October 2024. Result: The highest to lowest temporary blood donation deferral factors in male donor candidates, respectively, are due to high hemoglobin levels (69.6%), high blood pressure (16.4%), low hemoglobin levels (7.7%), low blood pressure (5.8%), and underweight (0.5%). For temporary blood donation deferral factors in female donor candidates, the highest to the lowest are, respectively, due to low hemoglobin levels (67.3%), low blood pressure (19.6%), high blood pressure (8.4%), underweight (3.1%), and high hemoglobin levels (1.6%). Keywords: Donor Selection, Temporary Blood Donation Deferral, Gender